Narrative and Semiotic Analysis on Hajj and Social Issues in Mecca I'm Coming Movie - Ali, Ahmad Jum'a Khatib Nur; Siddiq, Mohammad (Bina Nusantara University, 2023)
The research aimed to find out how the narrative and language signs of Hajj correlate with social issues in the Mecca I’m Coming movie. In Indonesian society, Hajj, as one of the Islamic pillars, was not only associated with religious values but also socio-cultural aspects. The research employed a textual approach, incorporating two analytical theories: narrative structure and semiotic signification. The narrative structure model by Lacey and Gilespie was used to ascertain the narrative structure, while Ferdinand de Saussure’s concept of signification was applied to investigate the meanings of the research object. Stuart Hall’s circuit of culture, referred to as the framework analysis model, deepens the study of the research data. The research data were visuals and verbal information related to Hajj and its connection with social issues. The result shows that the object has equilibrium, disruption, disruption (complication), climax, disequilibrium, and new equilibrium narrative structure. The correlation of Hajj and the social issues featured in the film is (1) Hajj as social status; (2) the portrayal of Hajj status as a favored choice for marriage that intensifies in the unfolding of the story’s plot, leading to conflicts and complex situation; lastly (3) the issues of the social media phenomena in the community that appears in a secondary plot in the story through two figures; Bagyo and Tuti.